2017
DOI: 10.11607/prd.2239
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Periodontal Biotype on Root Surface Exposure During Orthodontic Treatment: A Preliminary Study

Abstract: Aim: To evaluate the long-term outcomes of Acellular Dermal Matrix (ADM) with Coronally Advanced Flap (CAF) or Tunnel technique (TUN) in the treatment of multiple adjacent gingival recessions (MAGRs). Material and methods: Nineteen of the original 24 patients contributing to a total number of 33 sites for CAF and 34 for TUN were available for the 12 years follow-up examination. Recession depth, mean root coverage (mRC), keratinized tissue width (KTW), gingival thickness (GT) were evaluated and compared with ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
84
0
16

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(104 citation statements)
references
References 58 publications
(94 reference statements)
4
84
0
16
Order By: Relevance
“…Authors report an increase of the prevalence up to 47% in long‐term observations (5 years) . One study reported a correlation between lower incisor proclination and thin phenotype Direction of the tooth movement and the bucco‐lingual thickness of the gingiva may play important roles in soft tissue alteration during orthodontic treatment …”
Section: Mucogingival Conditions Around the Natural Dentitionmentioning
confidence: 99%
“…Authors report an increase of the prevalence up to 47% in long‐term observations (5 years) . One study reported a correlation between lower incisor proclination and thin phenotype Direction of the tooth movement and the bucco‐lingual thickness of the gingiva may play important roles in soft tissue alteration during orthodontic treatment …”
Section: Mucogingival Conditions Around the Natural Dentitionmentioning
confidence: 99%
“…The authors scored GT as thin, medium, or thick. Recently, a color‐coded probe was proposed to identify four gingival biotypes (thin, medium, thick and very thick) …”
Section: Case Definitionsmentioning
confidence: 99%
“…GT can be measured with different approaches, as reported previously. To date, a reproducible, and easy approach is observing a periodontal probe detectable through the soft tissues after being inserted into the sulcus …”
Section: Case Definitionsmentioning
confidence: 99%
“…1 When the gingival biotype is thin, orthodontic tooth movements may be considered unfavorable, increasing the risk of gingival recession. 2 Melsen and Allais 3 found significant correlations between keratinized gingival width, gingival biotype, and the development of or increase in gingival recession.…”
Section: Introductionmentioning
confidence: 98%
“…However they have focused mainly on the buccal plate of maxillary anterior teeth. 2,[12][13][14][15][16] To the best of the authors' knowledge, no studies have investigated the relationships between soft tissue biotypes and the buccolingual alveolar structures, particularly in patients with skeletal Class III malocclusion.…”
Section: Introductionmentioning
confidence: 99%